(3eaQL GdcQhH aj JGQjN Hfi CjhHs - (3eMeO Hf SGde Hf hGUd GdMehj, LeGd GdOjf , CHh YHO Gddg,J (B697 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYRjR GdZaGQ Gdbhi GdbgGQ s
(3BNQgG (B:s
(3jfJgi YfO MhGOK SfI (B617(3g` s
(3GfXQ HbjI fSN gPG GdcJGH ai GdbSe GdChd ef GdagQSJ HQbe (B503s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B133s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B153 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI ceHQOL s
Keywords: (3GdJGQjNs